A STUDY OF ENGLISH ORAL COMMUNICATION STRATEGIES USED AMONG THAI EFL STUDENTS OF DIFFERENT ENGLISH PROFICIENCY LEVELS: A CASE STUDY OF FIRST YEAR ENGLISH MAJOR STUDENTS, SRINAKHARINWIROT UNIVERSITY - Inkaew, Chanawan; Thumawongsa, Narathip (PEOPLE: International Journal of Social Sciences, 2018)
Being able to communicate effectively is the highest goal of all language learners. Most of people preferred to communicate orally, however, it is not easy for ESL/ EFL students to communicate proficiently (Surbhi, 2015). Therefore, Communication Strategies (CSs) are brought up to cope with the difficulties. This research aims to investigate CSs used in oral communication among Thai EFL students of different English proficiency levels: beginning, intermediate and advanced level, when speaking English in real context. The findings attempted to answer what CSs Thai EFL students of different levels utilize, and are there any significant differences of CSs used among the three levels students, and also between the students in Bachelor of Arts (B.A.) and Bachelor of Education (B.Ed.). The subjects were 89 first year English major students of Srinakharinwirot University which consisted of 70 B.A. students and 19 B.Ed. students. The obtained data were analyzed based on the framework of Communication Strategies proposed by Tarone (1977). The finding indicated that there were significant differences of CSs used among the different level students. However, the students of different programs did not have differences in the use of the CSs. It also showed the strategies that are least used by each level of students: Approximation by beginning, Language switch by intermediate and Topic avoidance by advanced. The finding in this study corresponded to the research of Chuanchaisit and Prapphal (2009) which reported that the advanced level students preferred risk taking strategies such as Circumlocution and Clarification request, whereas the beginning level tended to employ Topic avoidance and Body language. The results from this study will provide recommendations for English teaching and learning for communicative competence of EFL/ ESL students.